Exploring Digital Citizenship Awareness among Middle School Students in Surabaya: An Empirical Study on Current Perspectives and Educational Implications - Harmanto, Harmanto; Ghofur , Muhammad Abdul; Sukardani , Puspita Sari; Prahani, Binar Kurnia; Saphira, Hanandita Veda (International Journal of Emerging Research and Review, 2023)
Objective: To analyze the understanding of junior high school students in the city of Surabaya related to Digital Citizenship, which includes (1) digital access, (2) digital commerce, (3) digital literature, (4) digital ethics, (5) digital law, (6) digital rights and obligations, (7) digital health, and (8) digital security. Method: The approach in this study is Quantitative, with a survey design with research subjects of as many as 200 junior high school students in the city of Surabaya. The sampling technique uses a random area: West, North, East, and South.  Results: The critical importance of digital citizenship education in shaping responsible, ethical, and intelligent behaviour among students in the digital realm. The data indicates a high level of digital access, significant internet usage, and active involvement in various online activities. In this context, digital citizenship education emerges as a key factor in guiding students to navigate the digital world responsibly, understanding online ethics, and promoting a balanced approach to technology use. Novelty:  The absence of detailed insights into specific online activities and the limited data on students' awareness and engagement with emerging technologies, such as artificial intelligence.  Future research could explore specific online behaviours and reasons behind limited AI use, and conduct longitudinal studies to assess the long-term impact of digital citizenship education on students' behaviours.